Measuring and analyzing the impact of crude oil price on Stock Market Activities: Empirical Evidence from US - Mhamad, Shanaz Hakim (Sulaimani Journal for Humanities, 2022)
The aim of the paper is to measure and analyses the interactive relationship between the fluctuation of world crude oil prices, the real GDP growth, interest rate, exchange rate and the stock exchange of the United States. The crude oil prices and selected variables such as interest rate, exchange rate, and gross domestic product (GDP), are taken as independent variables while stock market is taken as dependent variable for US. To achieve this objective (of fulfilling its full potential), the present paper adopts OLS approach, and the secondary data was used for the period of 1990-2020, and multiple regression with its assumption were used in order to analyze data. Findings, exchange rate, real GDP, interest rate are very important determinates of Stock market in US because the p-value of those were less than the common alpha α =0.05. For instance, for each unit increasing of exchange rate, the stock market will increase by 1.767309 after holding all other variable constant. However, we find that there was no statistically significance between Crude Oil Price and stock markets with exchange rate.
Keywords: Crude oil price; Stock market; Macroeconomic variables; OLS; US